2021
DOI: 10.1097/sap.0000000000002710
|View full text |Cite
|
Sign up to set email alerts
|

External Splinting Is Not Mandatory After All Rhinoplasties

Abstract: Background Although casts or external splint materials are commonly applied on the external nose after rhinoplasty, their beneficial effects have not been previously demonstrated in controlled studies. Methods A total of 40 adult patients who underwent primary rhinoplasty were included in this prospective study. The patients were randomized into 2 groups to use an external splint or not after surgery. Only surgical taping was applied to the nasal dorsum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Modern rhinoplasty has undergone many changes from the time of its deemed father, Jacques Joseph, to the present day. 17 Today, the expectations of rhinoplasty patients are continuously increasing with the use of selfies in social media. In this sense, postoperative nostril and columellar symmetry are important for the reputations of rhinoplasty surgeons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern rhinoplasty has undergone many changes from the time of its deemed father, Jacques Joseph, to the present day. 17 Today, the expectations of rhinoplasty patients are continuously increasing with the use of selfies in social media. In this sense, postoperative nostril and columellar symmetry are important for the reputations of rhinoplasty surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Modern rhinoplasty has undergone many changes from the time of its deemed father, Jacques Joseph, to the present day 17 . Today, the expectations of rhinoplasty patients are continuously increasing with the use of selfies in social media.…”
Section: Discussionmentioning
confidence: 99%
“…Dieffenbach9 described 2 parallel l-cm-wide bilateral excisions that diminished the size of a very broad nose. Although controversial, according to many, Jacques Joseph, who is deemed the father of modern rhinoplasty, reported 43 patients whose nose shape improved only by skin excision 9,12–14. Peterson11 described the combination of intranasal rhinoplasty with flap lift of the nasal tip via nasal dorsal skin excision for a long, hooked nose in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…2 In an RCT of 40 patients randomized to receive either nasal splinting or only surgical taping postoperatively, the levels of periorbital edema and ecchymosis were significantly lower in the patients without splints (P < 0.05 for each). 12 The other three studies reviewed by Khan et al were retrospective case series of rhinoplasty patients who did not receive postoperative splints. [13][14][15] Across 2385 total patients, the collective results demonstrated that splinting was not necessary to achieve desirable aesthetic outcomes.…”
Section: Uses In Facial Surgerymentioning
confidence: 99%